Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/s2214-109x(17)30451-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of chronic obstructive pulmonary disease in the global population with HIV: a systematic review and meta-analysis

Abstract: None.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
96
3
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(109 citation statements)
references
References 65 publications
4
96
3
6
Order By: Relevance
“…PLWHIV who are current smokers have increased rates of respiratory symptoms, COPD and bacterial pneumonia, and mortality is significantly increased in current versus never smokers . Similarly, as in the meta‐analysis by Bigna et al [. ], we also found that older age was associated with increased odds of airflow obstruction.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…PLWHIV who are current smokers have increased rates of respiratory symptoms, COPD and bacterial pneumonia, and mortality is significantly increased in current versus never smokers . Similarly, as in the meta‐analysis by Bigna et al [. ], we also found that older age was associated with increased odds of airflow obstruction.…”
Section: Discussionsupporting
confidence: 86%
“…However, our prevalence is consistent with that found in a recently published systematic review and meta‐analysis by Bigna et al . based on 30 studies, which found an overall, global prevalence of COPD in PLWHIV of 10.5% (95% CI 6.2–15.7). They included studies that used a variety of methods for diagnosing COPD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bigna et al 2 seek to establish the type of relationship between HIV and chronic obstructive pulmonary disease (COPD), following a number of previous studies. They undertook a systematic review and meta-analysis of observational studies of COPD in HIV-positive individuals.…”
Section: Chronic Obstructive Pulmonary Disease In the Context Of Hivmentioning
confidence: 99%
“…This stimulation could lead to the production of inflammatory cytokines and chemokines, as well as proteases that cause tissue destruction, airway thickening, and clinical expression of COPD. The absence of an association between CD4 cell count and COPD can be explained by the fact that tissue inflammation count in COPD is characterized by the predominance of neutrophils, CD8 cells, and macrophages infiltration, rather than CD4 cell count [98].…”
Section: Hiv/aidsmentioning
confidence: 99%